Using Pop-Up Book in E-Learning to Improve Students Vocabulary Mastery Student - Riswalastika, Erva; Susanto, Dias Andris; Suwarti, T. Sri (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2023)
This research aims to test the effectiveness of using Pop-Up Books to increase students' vocabulary. Pop-Up Book is implemented for students in E-learning using YouTube videos. This research uses a quasi-experiment design with non-equivalent control groups. By conducting tests on two groups, this research design combines pre-test, treatment, and post-test research. The author uses a test for students created to measure student achievement in increasing vocabulary using Pop Up. Test to determine the difference in students' vocabulary mastery between the experimental group and the control group after the learning process using Pop-Up Books or without using Pop-Up Books. The population in this study were class VII students at MTs PSM Randublatung Blora for the 2021/2022 academic year. Two classes of class VII students at MTs PSM Randublatung, Blora, were used as samples. The control group is the first class, while the experimental group is the second class. Class VII C is the control group, while VII D is the experimental group. The results of this research indicate that the use of Pop-Up Books to increase students' vocabulary is effective. The test results show that the average score is 86.44, which is in the good range. With a rate of 59.03%, the use of Pop-Up Books as learning media is quite effective.